Znaczenie organizacji wirtualnych w zarządzaniu współczesnym przedsiębiorstwem - Piocha, Stanisław; Dylkiewicz, Renata Beata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
At the beginning of the current century modern production enterprises had strong vertical integration. This allowed to control the prices of components used in the production process, reduce fluctuation of deliveries and in fact to eliminate bargaining power of suppliers. The history of major companies confirms the thesis that they have lasting or transitory tendency to arrogance and falling into self-satisfaction. They become less flexible in reacting to customers' needs and are essentially sure that the customers shall adapt to them. It is both possible and favourable if the company runs like a lot of small companies. Every structural element of the organization would function on the basis of providing services to other. The condition of efficient functioning of a company in virtual environment is to possess proper IT management systems that are capable of functioning in a space of virtual organizations and to represent those organizations outside as well as to realize their goals. It is the virtual organization that may come up to the functions mentioned above. Then the philosophy of net organizations has to be consequently put into designing internal processes. There is a problem of legally determining the definition of virtual organization and to acquire such regulations to ensure that every participating party would have equal rights and gain proper effects according to their share. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 454-463